Estimate The Housing Gap In Syria And Studying The Economic And Demographic Variables That Effect In - Bshmani, Shakib; abokaff, Baraha’ (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The residential crisis considers urgent one of the problems which suffers from her the Syrian society, and that sight for lack of enough offered from the unities residential for coverage the increased request, and raved what importance estimate of this needs in scientific form confirms on Study of the favored variables economic and demographic in her. The searching to presence reached residential gap between the request on the unities residential and available from her this gap afforded with about 766803mskn during the period 1990-2010, just as the residential searching through the use of technicality the factorial analysis to accumulation changeable economic and demographic influential in the gap in five laborers managed she: The demographic laborer economic and the housing laborer and the general level the economist in the country and the laborer and the financial , laborer just as presence of impact appeared having statistical evidence for the economic variables and demographic on the residential gap in Syria. تعتبر الأزمة السكنية أحد المشكلات الملحة التي يعاني منها المجتمع السوري, وذلك نظراً لعدم كفاية المعروض من الوحدات السكنية لتغطية الطلب المتزايد, وهذا ما يؤكد على أهمية تقدير هذه الاحتياجات بشكل علمي ودراسة اثر المتغيرات الاقتصادية والديموغرافية فيها. وقد توصل البحث إلى وجود فجوة سكنية بين الطلب على الوحدات السكنية والمتوافر منها قدرت هذه الفجوة بحوالي 766803مسكن خلال الفترة 1990-2010, كما تمكن البحث باستخدام تقنية التحليل العاملي إلى تجميع المتغيرات الاقتصادية والديموغرافية المؤثرة في الفجوة السكنية بخمسة عوامل هي: العامل الاقتصادي والعامل الإسكاني والمستوى الاقتصادي العام في البلد والعامل الديموغرافي والعامل المالي, كما تبين وجود تأثير ذو دلالة إحصائية للمتغيرات الاقتصادية والديموغرافية على الفجوة السكنية في سورية.